2021
DOI: 10.1002/slct.202102204
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobized Short Peptide Amphiphile Functionalized Gold Nanoparticles as Antibacterial Biomaterials

Abstract: In search of new antibacterial agents and therapeutic strategies, during this antibiotic resistance crises, we developed a facile and effective antibacterial nanomaterial by using di‐phenylalanine based hydrophobized short peptide amphiphile (HsPA) and AuNPs. Such peptide amphiphile functionalised nanoparticles can provide a universal platform for medicinal applications owing to their unique physicochemical properties. The nanostructures of sPA and HsPA‐AuNPs hybrids were confirmed by spectroscopic and microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…One of the simplest method is the lipidation of a rationally designed short peptide‐based conjugates, leading to special class of peptide amphiphile, known as short peptide amphiphile (sPA) [26–28] . Thus, amyloidogenic dipeptide diphenylalanine (Phe‐Phe) was conjugated to a β‐amino acid i. e., β‐alanine (Scheme 1), which subsequently lipidated at N‐terminus by standard fatty acids, i. e., palmitic acid [29–30] . Such sPA have strikingly structural similarity to LPs and hence can be categorized into a simplified and updated version of LP [23] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the simplest method is the lipidation of a rationally designed short peptide‐based conjugates, leading to special class of peptide amphiphile, known as short peptide amphiphile (sPA) [26–28] . Thus, amyloidogenic dipeptide diphenylalanine (Phe‐Phe) was conjugated to a β‐amino acid i. e., β‐alanine (Scheme 1), which subsequently lipidated at N‐terminus by standard fatty acids, i. e., palmitic acid [29–30] . Such sPA have strikingly structural similarity to LPs and hence can be categorized into a simplified and updated version of LP [23] .…”
Section: Methodsmentioning
confidence: 99%
“…Such hybrid structures are comprised of electronically rich substituent, hence further make it a multifunctional hybrid nanomaterial reagent for numerous other applications ranging from nanotechnology to peptide‐based therapeutics [40–42] . It is also well documented that the presence of various metal ions are responsible to modulate the self‐assembled structures of this sPA 1 , and can be used for various biomedical application [29–30,40–42] . In our previous reports, the formation of nanostructures and their quantitative study for plausible applications were done in 500 μM [29] and 200 μM [30] ethanolic/aqueous‐ethanolic solutions of sPA 1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both sPA molecules, used in this study, were synthesized by following previously reported standard protocols. [18,20,24,[27][28][29] Firstly, we started to investigate the self-assembly of sPA1 and 2.…”
mentioning
confidence: 99%